LIPOLYTIC ACTIVITY IN LARVAL HAEMOLYMPH OF HELICOVERPA ARMIGERA (HUBNER) - PAWAR, AISHWARYA S.; GEJAGE, R.M.; DUBAL, R.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
Lipolytic activity in larval haemolymph of gram pod borer, Helicoverpa armigera (Hubner) revealed optimum pH 7.8, incubation time 20 minutes, temperature 37° C, enzyme concentration 1% and substrate concentration 6% and Michaelis-Menten constant 0.12 x 10-2 mM. The gradual increase in larval haemolymph lipase activity was observed from 7-day larvae to 10-day larvae and decrease from 10-day larvae to 15-day larvae. The maximum lipase activity was observed in 10-day larvae. The physiological role of larval haemolymph lipase (EC 3.1.1.3) of H. armigera has been reported in present paper.